Perbedaan Tingkat Kecemasan antara Siswa Sekolah Menengah Pertama Reguler dan Akselerasi di Sekolah Menengah Pertama Negeri 1 Wonogiri - Anindya Oktafiani; Mardiatmi Susilohati; Yulia Sari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Anxiety is the apprehension of something that will occur with uncertain causes. Class program differences may cause anxiety. In acceleration program, student are expected tobe more critical and creative given limited and targeted study time, but will likely be more anxious at a time due to tight competition. This research aims to find out whether anxiety level differs between regular students and accelerated students at SMP Negeri 1 Wonogiri. Method: This study was a descriptive analytical research using cross sectional approach conducted in March 2012 at SMP Negeri 1 Wonogiri. Subjects were purposively sampled based on the inclusion and exclusion criteria and were subsequently randomly sampled. Subjects filled in (1) curriculum vitae form, (2) L-MMPI questionnaire to find out the respondents' truthfulness in filling in the questionnaire, and (3) T-MAS questionnaire to measure the anxiety score. Subjects were excluded when their L-MMPI scores were ? 10 or did not fill in the questionnaire completely. Data were analyzed by Chi-square test using SPSS 17.0 for Windows. Result: Analysis fromeighty subjects showed a X2 value of 0.341, (p=0.599), meaning that there was no difference of anxiety level between regular and accelerated students at SMP Negeri 1 Wonogiri. Conclusion: There was no evidence of anxiety level differences between regular and accelerated students iat SMP Negeri 1 Wonogiri. Keywords: Regular program, Acceleration program, Anxiety